2021
DOI: 10.1155/2021/4245484
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Assisted Percutaneous Thrombin Injection for Treatment of Iatrogenic Left Subclavian Artery Pseudoaneurysm in a Critically Ill COVID-19 Patient

Abstract: Background. Central venous catheter represents an important tool in the management of critically ill patient. In this report, we described a COVID-19-positive case who had COVID-related complications and iatrogenic left subclavian artery pseudoaneurysm after central venous catheter insertion. Case Presentation. A 58-year-old male patient presented with a high-grade fever, myalgia, and shortness of breath due to COVID-19 infection. He required mechanical ventilation support and hemodialysis. He also developed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“… 7 When an arterial complication occurs, the management should be tailored to the patient's anatomy and condition. 6 According to Guilbert et al., 1 catheters of <7F located in compressible areas of the neck can be removed safely; otherwise, an intervention should be considered, In this case, a simple pull/pressure technique was not an option considering the CVC size (12F), the presence of a large pseudoaneurysm and its proximal localization. Open repair would have required a median sternotomy or thoracotomy to obtain a proximal control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 When an arterial complication occurs, the management should be tailored to the patient's anatomy and condition. 6 According to Guilbert et al., 1 catheters of <7F located in compressible areas of the neck can be removed safely; otherwise, an intervention should be considered, In this case, a simple pull/pressure technique was not an option considering the CVC size (12F), the presence of a large pseudoaneurysm and its proximal localization. Open repair would have required a median sternotomy or thoracotomy to obtain a proximal control.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The literature reporting iatrogenic SAP consists of few case reports. 4 , 5 , 6 Open surgical procedures including direct repair, ligation, or bypass are the most commonly described treatment, although, in high-risk patients, endovascular interventions or thrombin injections have been described as safe options. 6 In this case report, we describe a strategy involving the placement of covered stents and coiling to exclude an SAP.…”
mentioning
confidence: 99%
“…Delayed diagnosis can lead to long-term/permanent disability [134] Cancer therapy Thrombin DNA nanorobot with aptamer on the outside and thrombin in the internal cavity Tumor-specific intravascular thrombosis, leading to tumor necrosis and tumor growth suppression [157] Post-surgical cancer treatment Thrombin Sprayable thrombin solution and fibrinogen solution containing aCD47@CaCO 3…”
Section: Thrombin Used For Hemostasismentioning
confidence: 99%
“…Al-Thani et al reported a COVID-19 patient who developed complications related to SARS-CoV-2 infection and iatrogenic left subclavian artery pseudoaneurysm after central venous catherization. [134] With the ultrasound guidance, balloon-assisted percutaneous thrombin injection was applied. After 2 days, there was no flow in the pseudoaneurysm and the patient was extubated.…”
Section: Pseudoaneurysm Therapymentioning
confidence: 99%
“…Iatrogenic pseudoaneurysm is an exceedingly rare complication; Al-Thani et al presented one case of subclavian artery pseudoaneurysm induced by central venous catheter insertion [ 58 ]. The vessel wall weakness due to underlying endotheliitis secondary to both the COVID-19 virus itself in addition to vascular intervention/procedures might be the causative factor.…”
Section: Vascular Findings On Ct Angiographymentioning
confidence: 99%